IMPACT OF GLOBAL FOOD SECURITY INDEX ADJUSTMENTS IN THE CONTEXT OF MAJOR INTERNATIONAL CHALLENGES - Eduard BOGHIŢĂ; Ştefan VIZITEU; Dan DONOSĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Food security relies on interconnected social, economic, and biophysical systems to meet human nutritional requirements. Addressing risks is crucial for building resilience in food systems and ensuring long-term food security. Some major challenges include climate change, financial risks, and political instability. Resilience, the ability to bounce back from shocks, is increasingly important. To enhance long-term food security, we must build better food systems that can absorb and adapt to climate change and other risks. The proposed study aims to evaluate adjustments to the Global Food Security Index, providing recommendations for improving global food security policies. Identifying gaps in the Index and accurately reflecting the complexity of the global food system are essential outcomes. Access to affordable food is foundational for social well-being and stability. Higher-income households can better cope with temporary price increases, while low-income households require safety nets. The FAO Food Price Index reached an all-time high in March 2022, impacting developing countries facing challenges like the COVID-19 pandemic and resource inadequacy. Rising food prices before Russia’s invasion of Ukraine exacerbated the situation. Financial risks, currency depreciation, conflict, and political instability threaten food access. The Global Food Security Index revealed trends, including a decline in food affordability between 2019 and 2022. Additionally, agriculture’s expansion, particularly in developing countries, faces challenges due to degraded land. Soil health plays a critical role in food system resilience by retaining moisture and minimizing erosion and nutrient loss. Sustainable agricultural practices and natural resource protection are vital for long-term food security .